2002
DOI: 10.1007/bf03017412
|View full text |Cite
|
Sign up to set email alerts
|

QT interval and QT dispersion increase in the elderly during laparoscopic cholecystectomy: A preliminary study

Abstract: P Pu ur rp po os se e: : To compare the influence of a longer duration of intraperitoneal CO 2 insufflation with head-up tilt on electrocardiogram indices during laparoscopic cholecystectomy between elderly and younger patients.M Me et th ho od ds s: : Twelve elderly and 12 younger patients were studied. In all patients, intraperitoneal CO 2 insufflation was performed for more than 150 min in the head-up position. RR interval, QT interval, the rate-corrected QT (QTc) interval, QT dispersion (QTD) and the rate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 18 publications
0
19
2
Order By: Relevance
“…Because of the higher intrathoracic pressures, QTd and QTcd levels may be increased more in the high-pressure group than in the low-pressure group. Although Egawa and colleagues demonstrated that QTd changes were related to the duration of CO 2 insufflation during LC, we were not able to find such a relationship [8]. Increases in the mean QTc and QTcd in our series seemed to be independent of the duration of CO 2 insufflation.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Because of the higher intrathoracic pressures, QTd and QTcd levels may be increased more in the high-pressure group than in the low-pressure group. Although Egawa and colleagues demonstrated that QTd changes were related to the duration of CO 2 insufflation during LC, we were not able to find such a relationship [8]. Increases in the mean QTc and QTcd in our series seemed to be independent of the duration of CO 2 insufflation.…”
Section: Discussioncontrasting
confidence: 48%
“…Additionally, it is thought that surgical stress also affects QTd and QTcd [8]. Surgical exertion may prolong QT duration, but this effect was the same in both groups in our study.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Egawa et al [26] reported that QTd prolongation was connected to the longer duration of CO 2 insufflation during laparoscopic cholecystectomy. In the present study, because of there were no significant differences between the groups relating with hypercarbia, we were not able to find such a relationship between hypercarbia and QTd, QTcd or Pd.…”
Section: Discussionmentioning
confidence: 99%
“…However, QT dispersion (QTD), a value obtained by subtracting the minimum QT interval from the maximum QT interval as determined using a recorded 12-lead ECG, is considered an indicator of instability during ventricle repolarization. In addition, QT and QTD appear to correlate with autonomic regulation instability [4][5][6] and are potential causes of ventricular arrhythmias [7] or severe cardiac adverse events [8], such as myocardial infarction or cardiac sudden death [9][10][11][12][13]. In addition, several reports have indicated that both values increase as a result of various perioperative surgical procedures [14,15].…”
Section: Introductionmentioning
confidence: 99%